Curve normal labor in Peruvian women - Hurtado, H. (2015)
According to the criteria listed, 875 curves labor, to obtain the curve of labor in general they were transcribed. 400 gilts and 475 were multiparous. With additional requirements, 463 cases for the development of the ideal working curve delivery were selected. 164 were 299 gilts and multiparous. The labor curve obtained makes it easy to objectify the presence of a phase Latent and Active Phase, the latter formed by the sub-phases of acceleration, maximum acceleration and Desceleración. The sum of the latent phase Active constitute 1st. Period. 2nd. Period, is the classic second stage. Curves labor of gilts generally gilts ideals, general and multiparous multiparous ideals are different from each other, but considering the quality of the groups, working curves ideal birth are preferred, as representative of the curve Labor of Peru's population. According to the results, the diagnosis of Prolonged labor, occurs when its duration has exceeded 20 hours in first or 15 hours in multiparous. Prolonged Latent Phase, Phase Active prolonged dilation subnormal speed, etc.: with the same sense as concepts are introduced Estimated at extremely useful for the correct handling of labor.